Prognostic impact of diastolic dysfunction in systolic heart failure—A cross‐project analysis from the German Competence Network Heart Failure. Issue 9 (3rd May 2017) - Lüers, Claus; Edelmann, Frank; Wachter, Rolf; Pieske, Burkert; Mende, Meinhard; Angermann, Christiane; Ertl, Georg; Düngen, Hans‐Dirk; Störk, Stefan
Abstract : Background: We investigated the modifying role and prognostic importance of diastolic dysfunction (DD) in patients with heart failure and systolic dysfunction (SD). Hypothesis: The echocardiographic evaluation of diastolic function in patients with SD provides further prognostic information. Methods: From the German Competence Network Heart Failure, 1046 heart failure patients with reduced left ventricular ejection fraction (LVEF; <50%) were echocardiographically studied and followed for a median of 5 years. SD was subdivided into nonsevere (LVEF 36%–49%) and severe (LVEF ≤35%); DD was subdivided into nonsevere (E/E′ <15) and severe (E/E′ ≥15). Results: In general, severe SD was associated with higher hazard ratios (HRs; 2‐fold to 3.5‐fold) for all endpoints (all‐cause death, cardiac death, cardiovascular hospitalization, duration of hospitalization). Patients with severe SD had a 2.5‐fold risk of death (95% confidence interval [CI]: 1.84‐3.47, P < 0.001), and patients with severe DD showed a 1.8‐fold risk (95% CI: 1.17‐2.61, P = 0.004). Furthermore, we observed a strong interaction of SD and DD: concomitant severe DD in patients with moderate SD increased risk substantially (HR: 1.73, 95% CI: 1.16‐2.6, P = 0.007); by contrast, in patients with severe SD, additional presence of severe DD added little or no risk (HR for interaction: 0.5–1.2). Conclusions: In heart failure patients with reduced LVEF, the evaluation of diastolic function provides additional prognostic information. Although severe SD generally increased the risk for all endpoints, the degree of DD and its impact as a prognostic marker for overall and cardiovascular mortality appeared of particular relevance in subjects with nonsevere SD.